2009
DOI: 10.1016/j.ajhg.2009.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Genomic and Genetic Approaches Implicates IREB2 as a COPD Susceptibility Gene

Abstract: Chronic obstructive pulmonary disease (COPD) is the fourth leading cause of death worldwide and is influenced by both genetic determinants and smoking. We identified genomic regions from 56 lung-tissue gene-expression microarrays and used them to select 889 SNPs to be tested for association with COPD. We genotyped SNPs in 389 severe COPD cases from the National Emphysema Treatment Trial and 424 cigarette-smoking controls from the Normative Aging Study. A total of 71 autosomal SNPs demonstrated at least nominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
143
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 142 publications
(154 citation statements)
references
References 26 publications
9
143
2
Order By: Relevance
“…We noticed that the subjects included by the GWAS 5,6 and related replication studies 14,15 were only ever-smokers (current-smokers and/ or former-smokers), while we additionally included non-smokers in this study. In order to make it comparable between our results and that of previous studies and eliminate the effect of smoking on results, we conducted a smoking status-stratified analysis, in which the study population was stratified into groups of non-smokers (n ¼ 456), former-smokers (n ¼ 369) and current-smokers (n ¼ 542).…”
Section: Association Of Ireb2 and Chrna3/5 With Copd In A Chinese Hanmentioning
confidence: 99%
See 1 more Smart Citation
“…We noticed that the subjects included by the GWAS 5,6 and related replication studies 14,15 were only ever-smokers (current-smokers and/ or former-smokers), while we additionally included non-smokers in this study. In order to make it comparable between our results and that of previous studies and eliminate the effect of smoking on results, we conducted a smoking status-stratified analysis, in which the study population was stratified into groups of non-smokers (n ¼ 456), former-smokers (n ¼ 369) and current-smokers (n ¼ 542).…”
Section: Association Of Ireb2 and Chrna3/5 With Copd In A Chinese Hanmentioning
confidence: 99%
“…[5][6][7]11 Genomic DNA was extracted from blood using the commercially extraction kit (Tiangen Biotech Co., Ltd, Beijing, China) according to the manufacturer's instructions. Genotyping was carried out commercially by BGI (Shenzhen, China) using Sequenom's iPLEX SNP genotyping protocol developed for measurement with the MassARRAY mass spectrometer (Sequenom, San Diego, CA, USA).…”
Section: Snps Selection and Genotypingmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29][30] Genotyping methods and patterns of linkage disequilibrium (Table E1) within loci are described in the Methods section in this article's Online Repository. We have selected proxy-SNPs for unavailable SNPs in ALSPAC by using HapMap release 22 31 : rs975278 in SERPINE2 for rs729631 (r 2 5 1) and rs6734100 (r 2 5 0.82), rs17368659 in MMP12 for rs2276109 (r 2 5 1), and rs8109167 in TGFB1 for rs6957 (r 2 5 1).…”
Section: Single Nucleotide Polymorphism Selection and Genotypingmentioning
confidence: 99%
“…[43] However, this was not found to be consistent in certain populations such as Caucasians, where no correlation between ADAM33 polymorphism and COPD was identified. [44] Iron-responsive element-binding protein 2 (IREB2) and mRNA were found to be increased in the lung tissues from COPD patients compared with controls, [45] and evidence suggests that the IREB2 SNPs in association with COPD are SNP rs2568494, rs2656069, and rs12593229. [46] Though COPD is mainly caused by smoking, another investigation found that IREB2 may affect COPD independent of smoking.…”
Section: Loss Of Telomeresmentioning
confidence: 99%